Lugar, saber social e educação no campo: o caso da Escola Municipal de Ensino Fundamental José Paim de Oliveira, distrito de São Valentim, Santa Maria, RS. - Moura, Edinara Alves de (2009)
The present study has as objective to do a reflection about the education in the rural space, in the context of the place, giving emphasis to the social knowledge, present in the school's community of the Municipal Elementary School José Paim of Oliveira, in the District São Valentim, part of the city Santa Maria, RS. The present research had a qualitative approach, where there was the employment of the Dialectic method to investigate the importance of the rural school in the context of place; to recognize the social knowledge of the community from the school in study, pointing out its importance in the constitution of the culture in that place; to learn the social knowledge that give basis to the rural teacher's pedagogic practice, making a relationship with the teacher's initial and permanent formation. It is through the understanding and of the knowledge of the place, that the educators of the schools can compose their educational practices, in a way to respect and to learn from the involved communities. As we experience the school in study, in its pedagogic routine, it could be verified that as it demonstrates its Pedagogic Political Project (PPP), still today, it follows the pedagogic beginnings of the Project of School-Nucleus. It was verified that, theoretically there is the concern with the rural common knowledge, of characterizing the school as "of the countryside" and not just in the countryside", as demonstrated in its PPP, however, there is the challenge of transforming this knowledge in a member of the curriculum of the school. The pedagogic practice experienced in the school values the social knowledge, through events (horseback ridings, parties, parades, among others), historical rescue, as the one made on the Coachmen, (2002 and 2004). However, the rural schools in the city of Santa Maria are geographically in the countryside, but in their daily practice, contents, calendar, etc., the school's curriculum is the same of an urban school. In this context, it was verified there is the need of further study for the implantation of the Operational Guidelines for Basic Education of the Rural Schools. This presupposition was not confirmed at the school in study, because even with the efforts demonstrated by the teachers and directing team, it is not noticed a true identity with the rural space. Therefore, from the moment the school starts to follow the Guidelines for a rural education, it will start to fulfill its social role, the role of promoting the improvement of the life conditions in the field, respecting the specificity of the place, its culture, knowledge, forming people conscious of their responsibility in the rural community's development.